5-Aminolevulinic acid-mediated photodynamic activity in patient-derived cholangiocarcinoma organoids. (December 2020) - Fujiwara, Hiroaki; Takahara, Naminatsu; Tateishi, Keisuke; Tanaka, Mariko; Kanai, Sachiko; Kato, Hiroyuki; Nakatsuka, Takuma; Yamamoto, Keisuke; Kogure, Hirofumi; Arita, Junichi; Nakai, Yousuke; Kasuga, Masato; et al.
Abstract: Background: Accurate diagnosis of the disease extension of cholangiocarcinoma (CCA) is often difficult in clinical practice. The diagnostic yield of conventional pre-operative imaging or endoscopic procedures is sometimes insufficient for the evaluation of longitudinal spreading of CCA. Here we investigated the usefulness of 5-aminolevulinic acid (5-ALA) for the pre- or intra-operative diagnosis of CCA, using patient-derived organoids. Methods: Four CCA- and two adjacent tissue-derived organoids were established. After 5-ALA treatment, we assessed their photodynamic activity using fluorescence microscopy. Results: CCA organoids established from different patients showed diverse morphology in contrast to monolayer structures of non-tumor organoids, and had the ability to form subcutaneous tumors in immunodeficient mice. CCA organoids demonstrated remarkably high photodynamic activity based on higher accumulation of protoporphyrin IX as a metabolite of 5-ALA compared to non-tumor organoids (40–71% vs. < 4%, respectively). Importantly, cancer cell-specific high photodynamic activity distinguished the organoids originated from biliary stenotic lesions from those of non-stenotic lesions in a CCA patient. The high photodynamic activity did not depend on the expression profile of heme biosynthesis genes. Conclusions: Distinct 5-ALA-based photodynamic activity could have diagnostic potential for the discrimination of CCA from non-tumor tissues. Highlights: We established patient-derived organoids from CCA and adjacent tissues. CCA organoids recapitulated the characteristics of original tumors. CCA organoids showed higher 5-ALA-mediated photodynamic activity than non-tumor ones. 5-ALA based photodynamic diagnosis in CCA could be useful in the future.